Congenital pulmonary vein stenosis at an African tertiary care centre over a 25-year period - Lebea, Mamaila; Cilliers, Antoinette M.; Ntsinjana, Hopewell N. (SA Heart Journal, 2019)
Background: Congenital pulmonary vein stenosis (PVS) is a rare condition, which results from abnormal embryological incorporation of the common pulmonary vein into the left atrium. Methods: A retrospective descriptive case series study was conducted with the aim of describing the characteristics and outcome of children with congenital PVS at an African tertiary care centre over a 25-year period. A computerised paediatric cardiology database initiated in the early 1990s was sourced to identify patients, following which clinical records were retrieved and reviewed. Results: Five cases of congenital PVS were identified between January 1990 and January 2016 and accounted for 0.0007% of all congenital heart defects seen at the centre during the study period. The age at diagnosis ranged from 22 months - 13 years. Most patients presented with respiratory symptoms, with 2 patients presenting with recurrent haemoptysis. The diagnosis of PVS was confirmed by cardiac catheterisation and pulmonary angiography in all patients. All cases were right-sided unilateral PVS and all were associated with one or more congenital heart defects. Mild pulmonary hypertension and elevated capillary wedge pressures were found in all patients. Only one patient underwent specific surgery to relieve the PVS, which subsequently recurred. Another patient underwent a lobectomy following recurrent haemoptysis, but subsequently died of sepsis. Conclusion: Congenital PVS is a rare condition often associated with other congenital cardiac defects. Respiratory symptoms are common at presentation, with haemoptysis forming part of the presenting clinical spectrum, which is in keeping with the published literature. Elevated pulmonary artery pressures and increased ipsilateral pulmonary capillary wedge pressures are a common finding at catheterisation.